Dickie Bird's Britain - Bird, Dickie and Lodge, Keith (London Hodder & Stoughton, 2002)
With humour and affection Dickie Bird travels around Britain and details what he loves best about it. Some of those Dickie meets on his travels are celebrities and some are ordinary, but very special folk, from Sir Steve Redgrave to the proprietor of his favourite Pennine transport cafe.
Include Illustration
Keywords: Travel -- Great Britain -- Bird, Dickie, 1933-